From Policy to Practice: Evaluating the Impact of Entrepreneurial Support Programs on MSME Growth - Anggara, Tosa; Hanoselina, Yulia (Al-Qalam Institue, 2025)
This study aims to analyse the implementation of the Micro, Small, and Medium Enterprises (MSME) empowerment program and identify factors that inhibit its implementation. The study used a qualitative case study approach, with data collection through in-depth interviews, observation, and documentation studies. The results indicate that the program has been implemented based on a clear legal basis. Core programs include business management training, the development of new entrepreneurs, and the facilitation of halal certification. Obstacles encountered include budget constraints, low community participation, minimal marketing support, and product legality issues. This study recommends increasing cross-sector collaboration, strengthening post-training mentoring, and optimising digital technology to expand the market for MSMEs. This study offers implications for the importance of integrating practical entrepreneurship into the curriculum, strengthening post-training mentoring, and incorporating digital technology into learning. Vocational education needs to collaborate with the industrial sector and government to create relevant programs that prepare MSMEs to face the challenges of the global market.